Threats That Arise From Within: Changes in Error Processing and the Prospective Prediction of Everyday Avoidance - Claudia R. Becker; Richard Morris; Annmarie MacNamara (Biological Psychiatry Global Open Science, 2025)
Background: Errors are internally generated and can be harmful. Therefore, errors are considered endogenous threats. Like other forms of threat, errors receive increased processing in clinical anxiety, and enhanced error processing is predictive of anxiety onset in children. As is seen with other types of threat, avoidance of errors could also play a role in symptom worsening. Methods: Seventy-four participants (56 female, 18 male) with internalizing psychopathology completed self-report measures and a flanker task during electroencephalography (EEG) recording at baseline (time 1) and 1 year later (time 2). Time 1 EEG event-related potentials, the error positivity (Pe) and the error-related negativity (ERN), as well as changes in error processing over 1 year, were examined as predictors of everyday avoidance (i.e., avoidance of anxiety-provoking stimuli in the real world) at time 2. Results: Participants with greater elaborated processing of errors (Pe) at time 1 showed greater increases in everyday avoidance at time 2. This association was only evident for participants with reductions in early error processing (ERN) over the same time period, potentially indicating avoidance of errors in the laboratory. In addition, smaller time 2 ERNs were correlated with increased time 2 everyday avoidance. Conclusions: Heightened elaborative error processing (indicative of sensitivity to endogenous threat) is predictive of increased everyday avoidance over 1 year. However, how patients respond to heightened elaborative error processing at baseline—i.e., via blunting of early error processing over the following year—is critical in determining worsening of everyday avoidance.